Motivational development in the input-poor context of the MFL classroom - Lloyd, R (2021)
This dissertation explores student motivation for learning languages and how it develops in a secondary school in England. The MFL classroom faces obstacles such an inconsistent education policy, limited curriculum time, and negative attitudes, contributing to the well-documented decrease in MFL uptake at GCSE and A-Level. Using a mixed-methods cross-sectional design, this study collected questionnaire results from 70 students across all year groups and conducted semi-structured interviews with nine students in Year 7 and Year 12. Five motivational constructs were examined: integrative orientation, instrumental orientation, intrinsic motivation, attitudes towards the learning environment, and attribution. The results showed that overall motivation was surprisingly high, and all constructs were interrelated. Intrinsic motivation emerged as the most important for overall motivation and influenced all other constructs, but could also be influenced by the others, in particular the learning environment. There was evidence that motivation followed a U-shaped curve over time: decreasing over KS3 and then increasing again at GCSE and A-Level. Attribution appeared to behave slightly differently: while attributional tendencies were generally positive, some participants held contradictory views and attribution scores remained stable over time. There was tentative evidence that attribution plays a larger role in self-reported proficiency. To fully understand student motivation, it was necessary to consider the underlying factors of each construct which contributed to overall motivation uniquely for each participant. Instrumental orientation could be divided in two, since internalised and external instrumental drivers behaved differently. Motivation could mostly be conceptualised within the framework of the L2MSS which has not been previously used in this context. Pedagogical and research implications are offered.